Anti-obesity potential of Capparis spinosa flower bud extracts in 3T3-L1 adipocytes and in high fat diet induced obese rats - Kumaraswamy Athesh; Pemiah Brindha (Faculty of Pharmacy, Mahidol University, 2022)
Obesity is a raising pandemic and it needs alternative approaches to prevent or treat, as the existing approaches are not highly effective. In this context, the present study has been designed with the aim to investigate the anti-obesity potential of aqueous flower buds extract of Capparis spinosa L. (AFBECS) in 3T3-L1 adipocytes and in high fat diet (HFD) induced obesity thereby giving scientific validation to its traditional use. The 3T3-L1 preadipocytes were cultured and differentiated in DMEM in the absence and presence of various concentrations of AFBECS (25, 50, 100, 250 and 500 µg/mL) and the influence of the extracts on 3T3-L1 adipocyte viability and lipid accumulation were determined. The results showed that AFBECS maintained the viability of the 3T3-L1 adipocytes and also reduced the lipid accumulation in 3T3-L1 cells, dose dependently. In-vitro pancreatic lipase inhibition assay of AFBECS had shown moderate level of inhibition when compared with Orlistat. For in-vivo studies, HFD induced obese rats were treated with 100, 200 and 300 mg/kg of extracts for a period of 60 days using orlistat as standard drug. Anti-obesity potential was assessed using food intake, body weight, organ weights, adipocyte area, lipid profiles and many other blood biochemical parameters. Data of in-vivo studies revealed, significant reduction in body weight, fat-pad and organ weights of AFBECS treated animals. Altered levels of glucose, insulin, leptin, lipid profiles and antioxidant status were also normalized upon AFBECS treatment. These findings suggested that AFBECS was found to have prominent anti-obesity potential and exhibited its therapeutic efficacy by inhibiting adipogenesis, promoting lipolysis and ameliorating oxidative stress.